Removal of calcium hydroxide from simulated internal root resorption defects: a comparative evaluation of EDDY, iVac, Pulp sucker, passive ultrasonic irigation, and conventional techniques - Burçin Arıcan; Nihan Berkdemir; Ayşe Tuba Özalp Koca; Utku Can Kemeç; Taha Özyürek (BMC Oral Health)
Abstract Background This study evaluated the effectiveness of various irrigation techniques, including iVac, passive ultrasonic irrigation (PUI), Pulp Sucker (PS), EDDY and conventional syringe irrigation (CSI), in removing calcium hydroxide (CH) from simulated internal resorption defects. Methods Seventy maxillary central incisors with straight, single-rooted canals were selected. Root canal preparation was completed using instrumentation up to an apical size of 40/.04. Each tooth was split longitudinally along the bucco-lingual axis, and artificial internal resorption cavities were created 5 mm from the apex. These cavities were filled with CH paste, and the two halves of each root were bonded together using cyanoacrylate adhesive. The canals were then fully packed with CH. The specimens were divided into five experimental groups, each subjected to a different irrigation protocol: EDDY, PS, CSI, PUI, and iVac. Irrigation included sequential use of 2% sodium hypochlorite, 17% EDTA, and distilled water, with a total of 30 mL used over 4 min for each sample. The percentage of CH removed was assessed, and the data were analyzed statistically at a 5% significance threshold. Results All tested techniques left CH remnants within the simulated internal resorption defects. PUI and EDDY achieved significantly greater CH removal compared to PS, CSI, and iVac (p < 0.05). However, no significant difference was found between PS and CSI (p > 0.05). Conclusion Complete removal of CH from internal resorption cavities is challenging. However, PUI and EDDY showed superior efficacy and should be preferred over conventional syringe irrigation, iVac, and Pulp Sucker to optimize CH removal.